2013
DOI: 10.1371/annotation/4d347090-bca1-4184-a5d5-bc2d38baec7d
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Next-Generation Sequencing Reveals Significant Bacterial Diversity of Botrytized Wine

Abstract: While wine fermentation has long been known to involve complex microbial communities, the composition and role of bacteria other than a select set of lactic acid bacteria (LAB) has often been assumed either negligible or detrimental. This study served as a pilot study for using barcoded amplicon next-generation sequencing to profile bacterial community structure in wines and grape musts, comparing the taxonomic depth achieved by sequencing two different domains of prokaryotic 16S rDNA (V4 and V5). This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Leveau [23] found that Massilia was the dominant genus on Chardonnay, in our study, it was found that the Massilia in Syr was 8.62%, while in Cha it was just 0.50%. Sphingomonas can survive the wine fermentation process [25] and yet its impacts on wine organoleptic properties remain unknown.…”
Section: Bacterial and Fungal Taxa Distribution In The Grape Carposphmentioning
confidence: 99%
“…Leveau [23] found that Massilia was the dominant genus on Chardonnay, in our study, it was found that the Massilia in Syr was 8.62%, while in Cha it was just 0.50%. Sphingomonas can survive the wine fermentation process [25] and yet its impacts on wine organoleptic properties remain unknown.…”
Section: Bacterial and Fungal Taxa Distribution In The Grape Carposphmentioning
confidence: 99%